OXA-162, a novel variant of OXA-48 displays extended hydrolytic activity towards imipenem, meropenem and doripenem. (1st October 2013) - Kasap, Murat; Torol, Sinem; Kolayli, Fetiye; Dundar, Devrim; Vahaboglu, Haluk
Abstract : Context : Isolation and characterization of OXA-162, a novel variant of OXA-48. Objectives : Klebsiella pneumoniae isolate with decreased susceptibility to carbapenems was recovered from a Turkish patient. This study aimed at characterizing the carbapenem resistance determinants of this isolate. Materials and methods : Antibiotic susceptibility tests, analytic isoelectric focusing (IEF), cloning and sequencing were performed. Cloned β-lactamase was purified by means of preparative gel electrophoresis and the kinetic constants were determined under initial rate conditions. Results : The identified bla OXA-162 gene was located on a ca. 45-kb plasmid carrying a transposon consisted of two IS 1999-2 elements. OXA-162 differed from OXA-48 by a single amino acid substitution (Thr213Ala) which increased the catalytic efficiency ( k cat / K M ) of OXA-162 towards imipenem and meropenem. Also this substitution caused a gain of hydrolysis ability towards doripenem. Analysis of OXA-162 model implied that the amino acid change might generate an extension in the opening of the substrate entry site and might cause extended hydrolytic activity towards imipenem, meropenem and doripenem. Discussion and conclusion : OXA-162, a derivative of OXA-48 has enhanced catalytic properties.